EPHB4 Mutation Implicated in Capillary Malformation–Arteriovenous Malformation Syndrome: A Case Report. Issue 5 (21st July 2017) - Yu, JiaDe; Streicher, Jenna L.; Medne, Livija; Krantz, Ian D.; Yan, Albert C.
Abstract: Capillary malformation–arteriovenous malformation (CM‐AVM) syndrome, due to inactivating mutations in RASA1 in 68% of cases, is characterized by the development of cutaneous capillary malformations and arteriovenous malformations or fistulas; no known genetic etiology has been identified in patients with CM‐AVM syndrome without RASA1 mutations. We present the case of a child with RASA1 ‐negative CM‐AVM syndrome with a de novo missense mutation in EPHB4, a transmembrane tyrosine kinase receptor essential for vasculogenesis. Inactivating the mutation in EPHB4 has been shown to upregulate the mitogen‐activated protein kinase pathway and the mammalian target of rapamycin complex 1, possibly contributing to the development of vascular malformations.